2021
DOI: 10.1039/d0ta08179e
|View full text |Cite
|
Sign up to set email alerts
|

Interrelated interfacial issues between a Li7La3Zr2O12-based garnet electrolyte and Li anode in the solid-state lithium battery: a review

Abstract: Li7La3Zr2O12-based garnet (LLZO-BG) electrolyte has the advantage of strong thermal stability and hence can avoid the flammability problem of organic electrolyte solution. However, the solid-state lithium battery with LLZO-BG electrolyte...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 193 publications
0
29
0
Order By: Relevance
“…A series of strategies have been approached to improve the interface contact between metal electrodes and oxide ceramic electrolytes 14 , 15 . Static pressing was mostly employed to improve the physical contact between the metal anode and solid-state electrolyte to a certain extent, but the improvement effect of interface contact with acceptable interface impedance is limited 16 .…”
Section: Introductionmentioning
confidence: 99%
“…A series of strategies have been approached to improve the interface contact between metal electrodes and oxide ceramic electrolytes 14 , 15 . Static pressing was mostly employed to improve the physical contact between the metal anode and solid-state electrolyte to a certain extent, but the improvement effect of interface contact with acceptable interface impedance is limited 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Composite electrolytes generally exhibit flexibility, high ionic conductivity, and good contact with the electrode. Previous studies showed that dispersing inorganic fillers (such as SiO 2 , ZrO 2 , TiO 2 , and other non-Li + -conductive nanoparticles or Li 7 La 3 Zr 2 O 12 , Li 0.33 La 0.557 TiO 3 , and other Li + -conductive nanoparticles) in a polymer matrix can reinforce mechanical properties compared to pristine polymer electrolytes. Moreover, the particles are incorporated into the polymer matrix to affect the recrystallization kinetics of the polymer chain, thereby promoting the local amorphous region and improving the ionic conductivity of the lithium salt polymer system. , Because of the increased area of the amorphous region and the improvement of the interface between filler and polymer, the development of nanostructured fillers has been proven as an effective ongoing strategy to improve ion conductivity of polymer composite electrolytes. A representative work by Cui and co-workers has demonstrated a one-dimensional nanowire fillers using Li 0.33 La 0.557 TiO 3 , which is perovskite-type conductive lithium ion conductor, to enhance the bulk ionic conductivity of its polymer composite electrolyte. Such an improvement is contributed by the extended ion transport paths created from conducting nanowire filler in polymer matrix, which is better than that of composite made from traditional isolated distributed nanoparticles .…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Solid-state electrolyte with high Li ion conductivity and mechanical strength has also emerged owing to its excellent safety and inhibition of Li dendrite growth. 13,14 In addition, constructing composite anodes by melting or electroplating metallic Li into three-dimensional conductive host materials with large specic surface area and abundant pores shows unique superiority in reducing the local current density, relieving the volume expansion and achieving homogeneous Li plating and stripping even at high current densities. 15,16 Many kinds of skeletons including carbon-based, metalbased and polymer-based skeletons are widely used in the construction of composite Li anodes.…”
Section: Introductionmentioning
confidence: 99%